3MDR treatment in an adolescent with PTSD: a case report - Mariëlle Hoekstra; Nancy van Veelen; Jorien van Leeuwen; Mirjam J. Nijdam; Eric Vermetten (European Journal of Psychotraumatology, 2023)
ABSTRACTBackground: As Posttraumatic stress disorder (PTSD) in adolescents significantly impacts their well-being, effective treatment is of great importance. Little is known, however, about the novel, multi-modal virtual reality supported, exposure-based psychotherapeutic interventions such as 3MDR in this population.Objective: To describe the 3MDR treatment of an adolescent with PTSD who did not respond to previous exposure-based PTSD interventions.Method: A 14-year-old girl diagnosed with PTSD received six sessions of 3MDR embedded in family therapy.Result: The patient tolerated the 3MDR intervention very well. Personalized music and self-selected pictures appeared to be a good fit, contributing to enhanced engagement in and adherence to the therapy. She no longer met criteria for PTSD post-intervention, and at 18 months follow-up.Conclusion: This case report suggests that 3MDR has potential as a trauma treatment for adolescents with treatment-resistant PTSD.